(untitled) (Bulletin KNOB, 1990)
In may 1940 a bombardment almost totally destroyed the urban functions of Rotterdam’s town-centre. Already during the war, the rebuilding of the town was being characterized by a definitive break with the past. In present-day Rotterdam history contrasts sharply with the new. Because of their scarceness, the few monuments the new Rotterdam possesses symbolize the town’s history in the first place. This uniqueness requires a special approach at restoration, of which several cultural aspects are treated in this article. Thus the experience and interpretation of history in the built environment is highly subjective and determined by place, time as well as the cultural context. Buildings and townscape visualize history. To the small circle of historical specialists, buildings make the past manageable by means of scientific study and tradition. As recently became evident from the events in Eastern Europe, to the general public buildings can also show history in a very eloquent and emotional way. After World War II the Brandenburger Tor became the built proof of the drama which had taken place in Europe. At present the same building reflects hopeful notions on the future, making at once the usual considerations of the protection of monuments extremely comparative. The restoration of such a monument as part of the restoration of the town-centre is impossible, because then urban functions would be activated. It is exactly this missing of urban functions that makes the Brandenburger Tor a symbol. Thus the restoration of the town’s economical functions at the rebuilding of Rotterdam meant wiping out the events of may 1940 and a definitive break with the historical town. Because of their scarceness, historical elements hardly could be starting point at the town’s rebuilding. Besides Rotterdam did not have a tradition on the field of the protection of monuments. The view on their protection during the thirties differed from the present-day protection of townscape by only paying attention tot the individual monument and ensemble, but neglecting the relation between these buildings and the original pattern of streets. Next to antiquarian aspects one had to point at the technical and functional decay of Rotterdam’s pre-war inner town, which could only be stopped by large-scaled redevelopment plans. Monuments and townscapes lacking insights were mainly borrowed from modern architecture and town-planning. Appreciated by architect, local authorities and the population, also the international acknowledgement of these complexes stimulated the modernization of Rotterdam. Therefore the traditional lay-out of the first Rebuilding-plan by ir. W. G. Witteveen has been rejected. The final Rebuilding-plan, the so-called ’Basisplan 1946’ with the team headed by ir. C. van Traa applied the principles of New Building as much as possible. Only the monumental Church of St. Laurentius and a building complex on the Haringvliet have been preserved. Other objects, which are indicated on the map as ’extant buildings’ date from the 20th century and maintained their special function such as Townhall, Exchange and Library. For practical reasons the Basisplan accepted traditional elements like the streets and canals, which were laid out according to the plan Witteveen. Also the borders of the town-centre are traditionally adapted to the structure of the 19th century surrounding town. At the same time the Basisplan can be read as a spatial scheme, of which the actual townscape can constantly be adapted by successive users and designers. Although the Basisplan still formally is the plan for the town-centre many changes have been realized since 1946. In the course of almost 45 years one introduced a historical factor in this future-directed plan. The reconstructed tower of the St. Laurentius no longer is the only reflection of the disappeared town. 17th and 18th century houses as well as the Old Harbour have been restored. Time took care of replenishment of the monumental truce with pre-war buildings like Townhall and White House. The rebuilding of history within the history of rebuilding is a new theme. Restoring registrated monuments the municipality of Rotterdam always consistently restored these buildings into their original form. A highly acceptable view, for these buildings have to represent history without support of the environment.